Ethics and Science: Challenges and Possibilities - Hajko, Dalimir (Communications - Scientific letters of the University of Zilina, 2017)
Perhaps the biggest challenge for the relationship of ethics and science is the issue of whether or not it is justifiable to manage human related research (for example, the question of whether we should have a moratorium on research that constitutes dangers to human being and/or humanity) socio-ethically. The author asks the question if such management is principally possible. Scientism and socio-ethical nihilism have increased their influence which manifests itself, among other things, in attempts to seclude ‘a unique ethics of science’ based on objective postulates of knowledge alone, separated from social praxis as well as from ethical values of humanity. Related to this situation is the fundamental question whether an ethical ‘self-regulation’ of science, detached from social factors that are foundational for such regulation, is at all possible. Science in and of itself does not enter into a contradiction with some abstract ethical norms: a conflict can only be induced by a specific form of its functioning in relation to concrete historic demands of morality. Another important starting point for our deliberation on this topic is the question what makes (or motivates) scientists concern themselves with moral or social problems of regulating the scientific knowledge and scientific or technological praxis? In addition to a rapid growth of scientific and technological possibilities and the ensuing serious problems of social responsibility, it is also the non-existence of such social institutions that would be able to ensure an effective and sufficiently flexible regulation of scientific research, i.e. institutions that would make it possible to diminish the gap between the interests of science and its socio-ethical consequences. Conclusion: there is no secluded, particular ethics of knowing that would be based on an abstract concept of the objectivity of science.